Hasil Review Trade Policy Review Body WTO sebagai Unilateral Act of an International Organization - Simbolon, Putu George Matthew (Universitas Semarang, 2023)
This seeks to provide an understanding concerning the Trade Policy Review Body (TPRB) review perceived as a unilateral act of an international organization. The article is written based on the normative method through the application of doctrinal, conceptual, and case approaches. Furthermore, this article is also written by gathering primary and secondary legal sources. The article herein consists of three parts. The first part discusses the unilateral act as the source of international law as one of the international law norms outside the Article 38 paragraph (1) ICJ Statute. Meanwhile, the second part explains the weaknesses of TPRB which caused this organ unable to work under its effective means. Furthermore, the third part explains how the matters under the TPRB review outcome shall be conducted so that such a product can be qualified as a unilateral act applicable by WTO members under good faith. Based on the three discussions therein, this article suggests that the TPRB review outcome shall be perceived as a unilateral act of an international organization. Such perception can be actualized by applying imperative sentences in adopting the review outcome that will be issued for the reviewed member. Penelitian yang dijelaskan pada artikel ini bertujuan untuk menyediakan pemahaman mengenai bagaimana hasil review dari Trade Policy Review Body (TPRB) dapat dikualifikasi sebagai tindakan sepihak oleh organisasi internasional (unilateral act of an international organization). Artikel ini ditulis dengan menerapkan metode penelitian normatif melalui pendekatan doktrinal, konseptual dan kasus. Adapun bahan hukum yang digunakan yaitu bahan hukum primer dan sekunder. Artikel ini terdiri dari tiga bagian. Bagian pertama membahas tentang unilateral act sebagai salah satu hukum internasional yang tidak diatur di dalam Article 38 paragraph (1) ICJ Statute. Bagian kedua dari artikel ini kemudian menjelaskan tentang kelemahan dari TPRB yang membuat organ ini tidak dapat bekerja dengan efektif untuk saat ini. Kemudian bagian ketiga menjelaskan tentang kalimat yang harus digunakan dalam menyusun materi muatan hasil review TPRB agar produk tersebut dapat menjadi tindakan unilateral yang harus diterapkan oleh anggota WTO dengan iktikad baik. Berdasarkan tiga pembahasan tersebut, artikel ini menyarankan agar hasil review TPRB harus dipandang sebagai tindakan unilateral. Pandangan tersebut dapat diwujudkan melalui diterapkannya penyusunan kalimat imperatif pada laporan yang akan diterbitkan kepada anggota yang direview.